Exploitations of Embodiment: Born Freak and the Academic Bally Plank - Mitchell, David; Snyder, Sharon (Disability Studies Quarterly, 2005)
Freak show scholars must openly wrestle with the degree to which they imagine that one can learn something about disability by analyzing the social relations that constitute freak show exhibition. This is partially a question of the degree to which one believes that scholarly commentary can effectively divest interest in freak spectacle from an exploitative relationship. Additionally, one's relationship to this issue tends to rely upon whether the scholarly approach applied theorizes disability as unbridgeable difference from normativity or artificial augmentation of mere human variation into monstrous other. In order to probe this arena of thought — and reflect critically on the utility of the freak show for understanding the contemporary predicament of disabled people — we pursue an extended close reading of Mat Fraser's documentary film, Born Freak (2002), as a productive interrogation of extant critical traditions on the freak show. Born Freak literally takes up applications of various modes of freak show address as if it seeks to try on each one and assess its utility. The film employs its visual terrain as if it were an experimental lab where one can interrogate the pragmatic utility of each paradigm. Interestingly, Born Freak helps to expose the limits of current theories through Fraser's investigation into the experience of a contemporary disabled actor-turned-freak.